Translations and Rewritings of Hamlet in Indonesia - Diana Hardiyanti; Riyadi Santosa; M.R. Nababan; Mugiyatna Mugiyatna (Universitas Muhammadiyah Semarang, 2022)
Exploration of local adaptations of Shakespeare's plays around the world has been one of the most prolific disciplines of Shakespeare studies in the last two decades. The local appropriation of Shakespeare’s Hamlet has led to challenging the Indonesian translators to reproduce the masterpiece work of William Shakespeare for the local reader. Hamlet has several translated versions in Indonesia, from the early translation by Trisno Sumarjo (1950), Santiko Budi (2009), and then more contemporary translation by Fatimah, Ifa Nabila and Ratna Ofvilia (2018). This article looks at translations and rewriting of Hamlet in Indonesia. It explores how the rewriting process happens and the functions that Hamlet has served for the Indonesian reader: a rite of passage and an educational tool of literary works for students. It is also elaborate concept of Susan Bassnett and André Lefevere’s ideas about translation and rewriting at work. how the translators react to the ideas and references of the source cultures’ myths and belief systems and rewrite them to fit the target reader